Investigation of decision-making under uncertainty in healthy subjects: A multi-centric fMRI study - Krug, A.; Cabanis, M.; Pyka, M.; Pauly, K.; Walter, H.; Landsberg, M.; Shah, N. Jon; Winterer, G.; Wölwer, W.; Musso, F.; Müller, B.W.; Wiedemann, G.; et al. (Behavioural brain research, 2014)
•Sixty-four healthy subjects in a multi-centric fMRI study.•Information gathering was correlated with a network of prefrontal and parietal cortex.•Reaching a decision was correlated with medial prefrontal cortex and precuneus.•Uncertainty acceptance activated a network of the frontal cortex and insula.•Uncertainty avoidance was correlated with the right middle frontal cortex. Decision-making is an everyday routine that entails several subprocesses. Decisions under uncertainty occur when either prior information is incomplete or the outcomes of the decision are unclear. The aim of the present study was to disentangle the neural correlates of information gathering as well as reaching a decision and to explore effects of uncertainty acceptance or avoidance in a large sample of healthy subjects. Sixty-four healthy volunteers performed a decision-making under uncertainty task in a multi-center approach while BOLD signal was measured with fMRI. Subjects either had to indicate via button press from which of two bottles red or blue balls were drawn (decision-making under uncertainty condition), or they had to indicate whether 8 red balls had been presented (baseline condition). During the information gathering phase (contrasted against the counting phase) a widespread network was found encompassing (pre-)frontal, inferior temporal and inferior parietal cortices. Reaching a decision was correlated with activations in the medial frontal cortex as well as the posterior cingulate and the precuneus. Effects of uncertainty acceptance were found within a network comprising of the superior frontal cortex as well as the insula and precuneus while uncertainty avoidance was correlated with activations in the right middle frontal cortex. The results depict two distinct networks for information gathering and the indication of having made a decision. While information-gathering networks are modulated by uncertainty avoidance and – acceptance, underlying networks of the decision itself are independent of these factors.